Rhinoceros Serum microRNAs: Identification, Characterization, and Evaluation of Potential Iron Overload Biomarkers - Wojtusik, Jessye; Curry, Erin; Roth, Terri L. (Frontiers in Veterinary Science, 2021)
Iron overload disorder (IOD) in critically endangered Sumatran (Dicerorhinus sumatrensis) and black (Diceros bicornis) rhinoceros is an over-accumulation of iron in organs which may exacerbate other diseases and indicate metabolic disturbances. IOD in rhinos is not well understood and diagnostics and therapeutics are limited in effectiveness. MicroRNAs (miRNAs) are small non-coding RNAs capable of altering protein synthesis. miRNA expression responds to physiological states and could serve as the basis for development of diagnostics and therapeutics. This study aimed to identify miRNAs differentially expressed among healthy rhinos and those afflicted with IOD or other diseases (“unhealthy”), and assess expression of select miRNAs to evaluate their potential as biomarkers of IOD. miRNAs in serum of black (n=11 samples; 5 individuals) and Sumatran (n=7 samples; 4 individuals) rhinos, representing individuals categorized as healthy (n=9), unhealthy (n=5), and afflicted by IOD (n = 3) were sequenced. In total, 715 miRNAs were identified, of which 160 were novel, 131 were specific to black rhinos, and 108 were specific to Sumatran rhinos. Additionally, 95 miRNAs were specific to healthy individuals, 31 specific to unhealthy, and 63 were specific to IOD individuals. Among healthy, unhealthy, and IOD states, 21 miRNAs were differentially expressed (P ≤ 0.01). Five known miRNAs (let-7g, miR-16b, miR-30e, miR-143, and miR-146a) were selected for further assessment via RT-qPCR in serum from black (n=61 samples; 7 individuals) and Sumatran (n = 38 samples; 5 individuals) rhinos. let-7g, miR-30e, and miR-143 all showed significant increased expression (P ≤ 0.05) during IOD (between 1-2 years prior to death) and late IOD (within 1 year of death) compared to healthy and unhealthy individuals. miR-16b expression increased (P ≤ 0.05) in late IOD, but was not different among IOD, healthy, and unhealthy states (P > 0.05). Expression of miR-146a increased in IOD and late IOD as compared to unhealthy samples (P ≤ 0.05) but was not different from the healthy state (P > 0.05). Selected serum miRNAs of black and Sumatran rhinos, in particular let-7g, miR-30e, and miR-143, could therefore provide a tool for advancing rhino IOD diagnostics that should be further investigated.